ANALISIS PENGARUH EMOTIONAL QUOTIENT (EQ) DAN STRES KERJA TERHADAP PERFORMA KERJA KARYAWAN PADA PT. BANK MESTIKA DHARMA MEDAN - Bambang, Bambang; Lumbanraja, Prihatin (Jurnal Ekonomi Modernisasi, 2013)
Human Resources are a generator of available resources in the activities and routine of an organization or company that the good and the bad performance of an organization are determined by the performance of human resources. Professional employee is a reliable employee with balanced quality between academic and emotional capability. Academic intelligence is frequently given a higher position than emotional intelligence is an individual evaluation. Emotional intelligence is the factor determining the effectiveness of someone is working that with high emotional intelligence, the human resources can be easily directed and guided to work in accordance with the goals of organization. The prupose of this quantitative descriptive explanatory study was to look at the influence of Emotional Quotient (EQ) and Work Stress on the performance of the employees of PT. Bank Mestika Dharma Medan using the theory of human resources management related to Emotional Quotient (EQ), work stress and work performance. The population of this study was 585 employees and 238 of them were selected to be the samples for this study. The data obtained were analyzed through multiple linear regression tests using F test to simultaneously test the hypothesis and using t test to do a partial test. The result of the hypothesis test showed that simultaneously the variable of Emotional Quotient and work stress had a significant influence on the improvemnet of the performance of the employees of PT. Bank Mestika Dharma Medan